"It's an Old House and That's How It Works": Living Sufficiently Well in Inefficient Homes. Issue 4 (2nd October 2019) - Roberts, Erin; Henwood, Karen
ABSTRACT: In the United Kingdom, the domestic sector is a major contributor of national carbon emissions. Improving the energy efficiency of the existing stock, particularly the oldest and least efficient homes, is therefore of utmost importance if ambitious carbon reduction targets are to be met. Analyzing the rich, narrative data of households living in old, hard-to-treat homes, this paper produces novel insights into the ways in which domestic thermal comfort practices are shaped by meaningful relationships, intimately bound to identificatory positions, that are deeply connected to these valued domestic environments. Findings concern how households renegotiate widely accepted understandings of thermal comfort to better fit with the materiality of their old homes by constructing for themselves meaningful 'moral' identities that focus on living sufficiently well. This relational understanding of domestic energy consumption highlights how materiality, practices and moral narratives are produced and reproduced dynamically over time.